2017
DOI: 10.1002/2017gc006888
|View full text |Cite
|
Sign up to set email alerts
|

Regional‐scale development of opening‐mode calcite veins due to silica diagenesis

Abstract: The formation and distribution of natural fractures in Cretaceous‐Paleogene strata in Jordan are strongly tied to diagenetic processes, which in turn reflect the lithology of the host material. Observations collected from subsurface cores show that widespread fracturing began before compaction of the host sediment was complete, based on ptygmatic folding of one set of mineral‐filled fractures (veins). Nonfolded veins are preferentially developed within heavily cemented layers. Calcium carbonate is the greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…An important example is ptygmatic folding of steeply dipping cement-filled fractures in sedimentary rocks. Such ptygmatic folds have been interpreted to form by compaction of the fracture, implying that the sediment fractured well before the consolidation process was complete (Hiscott, 1979;Karner and Shillington, 2005;Gale, 2014;Hooker et al, 2017a).…”
Section: Field Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…An important example is ptygmatic folding of steeply dipping cement-filled fractures in sedimentary rocks. Such ptygmatic folds have been interpreted to form by compaction of the fracture, implying that the sediment fractured well before the consolidation process was complete (Hiscott, 1979;Karner and Shillington, 2005;Gale, 2014;Hooker et al, 2017a).…”
Section: Field Evidencementioning
confidence: 99%
“…Fluid overpressure from organic matter maturation, derived from local organic components, drove fracture opening in layer-parallel fibrous calcite veins (Jochum et al, 1995;Zhang et al, 2016;Meng et al, 2017a) and at least assisted the opening of vertical fractures, whose orientation was likely controlled by regional tectonics (Hooker et al, 2017b). Volume loss from early silica diagenesis drove the opening of vertical, mudrock-hosted calcite veins (Hooker et al, 2017a). Meng (2017b) showed that the intensity of vertical and layer-parallel fibrous gypsum veins correlates directly with the amount of sedimentary gypsum in the host strata.…”
Section: Fracturing Fluids and Diagenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Although volume changes associated with reactions are likely to be unimportant in many natural fracture systems in which the most volumetrically significant fracture cements are quartz and carbonate minerals, host rock volume changes may be important in some fine‐grained, porous carbonate rocks and shales. Numerical modeling (Okamoto & Shimizu, ) and mineralogical observations (Hooker et al, ) suggest that fractures resulting from volume‐decreasing reactions can increase permeability and facilitate continuance of reactions causing fracture, via increasing reactive surface area in contact with fluids. In other words, fracture strain makes physical space for fluid access and reactant minerals.…”
Section: Questions For Future Researchmentioning
confidence: 99%